Caracterización óptica y estructural de monocapas de silicio poroso por medio de reflectancia en la región visible y rayos X - Roque Huanca, Danilo (2019)
A porous silicon monolayer with porosity varying in depth was characterized using different optical methods. The results show that techniques based on reflectance in the visible region diverge in approximately 20% of those found by means of X-ray based methods. This divergence is associated to the wavelength dependence of the refractive index of both the porous structure and the infiltrated liquid inside the pores. The results suggest that the porous structure can be modeled as a set of spherical pores with radius ranging from 3.0 to 4.4 nm, in addition to cylindrical pores with radius and length varying between 22 and 42 nm, while its length does between 55 -102 nm. The porosity of the structure varies in depth between 65-81%.